The Value of Serum Fibrinogen/Uric Acid Ratio as a Novel Marker of Fetal Growth Restriction in Preeclampsia at 34 Weeks - Nori, Wassan; Ibrahim Ali, Alaa; Ismael, Wisam A. (Current Women's Health Reviews, 2023)
Background: Fetal growth restriction (FGR) is a common alignment that complicates pregnancy, especially for preeclampsia cases; therefore earlier detection is crucial to improve the outcome. Objective: We examine whether the ratio of maternal serum fibrinogen to serum uric acid (ms F/U) can serve as a marker FGR in patients with preeclampsia at 34 weeks. Material and Methods: A cross-sectional study recruited 98 preeclamptic primigravidae at the University Teaching Hospital from June 2018 to June 2019. Patients were sent for laboratory and ultrasound examinations. Maternal parameters include systolic and diastolic blood pressure, serum fibrinogen, and serum uric acid. Ultrasonic fetal parameters include amniotic fluid index AFI, estimated fetal weight EFW, pulsatility index PI, and resistance index RI. Results: Pearson’s correlation between ms F/U ratio and all other feto-maternal variables was significant as P value was <0.0001. The ms F/U ratio showed strong positive correlations with EFW and AFI. The ms F/U ratio showed strong inverse correlations with PI, RI, systolic, diastolic blood pressure, and albumin/creatinine ratio. The strength of association tested by a coefficient of Mallow showed the strongest association between ms F/U versus fetal weight. The highest Odd ratio for FGR was 45, associated with the ms F/U ratio. The cutoff value for ms F/U ratio was 26.08 mg/dL with an estimated sensitivity and specificity of 85% and 96.25%, respectively, with an AUC of 0.82. Conclusion: Strong and significant correlation of ms F/U ratio with feto-maternal parameters at high sensitivity and specificity added to its simplicity, and cost-effectiveness makes ms F/U ratio a reliable marker for earlier FGR to improve the outcome.
Keywords: marker